ANALYSIS OF PRODUCT POSITIONING ON SOAP PRODUCTS IN MANADO - Megawe, Windy (Universitas Sam Ratulangi, 2013)
Business competition has become one main issue that is essentially considered by management parties in every company in a market, either manufacturing-based company or service-based company. When any competed company can establish or even maintain its core advantages against other competitors, it can later help its management parties to keep the company achievement and therefore give positive contribution for its further development in the marketplace. Research objective is to describe the product position from Lux, Lifebuoy, Shinzui, Dove, Nuvo, Dettol, Imperial Leather and Giv products in Manado. Theories supporting this research are positioning and brand. The population is all users of Lux, Lifebuoy, Shinsui, Dove, Nuvo, Dettol, Imperial Leather and Giv products in Manado with sample of 100 respondents. AnalysisÂ method used is Multi Dimensional Scaling and Correspondence Analysis. Results and conclusions are (1) Shinzui and Dettol are perceived similar, (2) Lux, Lifebuoy, and Dove are perceived similar, (3) Giv and Imperial Leather are perceived similar, and (4) Nuvo is very dissimilar with the other brands. Keywords: product positioning